Modulus Inversion Layer by Layer of Different Asphalt Pavement Structures - Mingming Cao; Wanqing Huang; Yiwen Zou; Guomin Liu (Advances in Civil Engineering)
In order to improve the accuracy of modulus inversion of the pavement structure layer, a layer-by-layer inversion method was proposed to be compared with the traditional inversion method by inverting the modulus of each structural layer of the inverted asphalt pavement and semirigid asphalt pavement. The results show that the influence of cushion modulus on the modulus of inverted subgrade and modulus of cement-stabilized crushed stone is restricted by the cushion modulus and pavement structure characteristics, and the thicker cement-stabilized crushed stone layer is beneficial for improving inverted modulus of subgrade; besides, for the inverted asphalt pavement, the modulus of the graded crushed stone transition layer has a significant influence on the modulus inversion of cement-stabilized crushed stone. The modulus of the graded gravel transition layer inverted by these two methods is underestimated, the modulus of cement-stabilized gravel is overestimated using the traditional inversion method, and the inversion result of the inverted asphalt pavement is more significantly affected by the inversion method than the semirigid base asphalt pavement. Moreover, the modulus of the pavement structural layer is determined by the material and structural characteristics, and its recommended empirical value or the value in the indoor test does not conform to the actual value of the site; by contrast, the inversion modulus obtained using the layer-by-layer inversion method is closer to the actual value, which can be used in the design of similar pavement structures to accumulate data for determining the material modulus or the pavement structure adjustment coefficient in the pavement structure.